If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(4+x)+5-3x+5x=
We move all terms to the left:
6(4+x)+5-3x+5x-()=0
We add all the numbers together, and all the variables
6(x+4)-3x+5x+5-()=0
We add all the numbers together, and all the variables
2x+6(x+4)=0
We multiply parentheses
2x+6x+24=0
We add all the numbers together, and all the variables
8x+24=0
We move all terms containing x to the left, all other terms to the right
8x=-24
x=-24/8
x=-3
| 2x+4+x=15+6x-2 | | 4(8–2v)=112 | | -17c+12=4c+18c | | 5x-10=2x+5ç | | b+315=204 | | 8=q-15 | | 420n=680 | | 48-y=158 | | 17v=99 | | b-46/4=10 | | 4/3w=−12 | | 17v=98 | | 6x+15=23x | | -4(3b+4)=-27-11b | | b-205=723 | | 17v=97 | | 2x+6+4x-2=11x-6 | | 6=-y+182 | | 17v=96 | | 3v+2=8v= | | 3(u+1)=18u= | | -86=x+4(-7x-8 | | 7.5x+11-3.5=35 | | 17v=90 | | 5y-26=y+50. | | k-77/5=4 | | 8/12=h/9 | | 17v=95 | | 43 w=−12 | | 3x+x+0.5x+180+1.5x=455 | | 4x-2-11x-6=2x+6 | | 94=9b+4 |